THU0166 Usefulness of the Acid Dissociation in Inmunogenicity Detection in Patients in Treatment with Anti-TNF Drugs. (10th June 2014) - Llinares-Tello, F.; Rosas, J.; Senabre-Gallego, J.M.; Molina, J.; Salas, E.; Santos-Soler, G.; Santos Ramírez, C.; Ortega, R.; Barber, X.; Pons, A.; Cano, C.; Lorente, M.; et al.
Abstract : Objectives: To evaluate the application in clinical practice, of the acid dissociation in the patients' monitoring with subtherapeutic serum concentrations of infliximab (IFX), adalimumab (ADL) and etanercept (ETN), using an immmunoassay (ELISA) commercialized (Promonitor®, Proteomika S.L.). Methods: For 3 years 499 trough samples were analyzed of 218 patients with different rheumatic pathologies treated with IFX (30 patients, 80 samples), ADL (116 patients, 238 samples) and ETN (72 patients, 181 samples). With the standard technology ADA was detected in 27, 16 and 0% of the patients treated with IFX, ADL and ETN respectively, coinciding always with a level of undetectable drug. 76 samples quantified with detectable but subtherapeutic levels at the standard treatment (26 samples of 20 patients with IFX <2 mg/L, 32 samples of 22 patients with ADL <3 mg/L and 18 samples of 15 patients with ETN <2 mg/L), that were analyzed for ADA after submitting them to an acid pre-treatment. The protocol of acidification consisted of the incubation of the serum during 15 minutes with acetic acid 300 mM and later neutralization with Tris 1 M fitting to a final dilution 1/10. Results: With the protocol of acid dissociation anti-ADL antibodies were detected in 55% of the patients with subtherapeutic levels of ADL, which were undetectable with the standard assay (17 samples, 12 patients, middle age: 55 years, 67% women, diagnoses: 8 ankylosing spondylitis (BASDAI:4, 8±1, 5), 3 rheumatoid arthritis and 1 psoriasic arthritis (DAS28: 3, 5±0, 2). In 7 cases ADA's detection after acidificatiόn was produced already in the first request of monitoring to 6 months of initiated the treatment. In other 3 cases, ADA's positive after dissociation confirmed a previous positive with the standard assay. Initially the treatment was kept with ADL in 5 patients, which ended up by turning out to be positives with the standard technology between 2 and 6 months after the positive with dissociation. Finally, in 12 patients a change of treatment was necessary for lack of clinical response, being chosen by another anti-TNF before ADA's evidence. ADL's maximum concentration in the samples with a positive result was of 1, 8 mg/L and the title of detected antibodies ranged between 35 and 282 UA/mL. Anti-IFX not anti-ETN antibodies were not detected after the acidificaciόn of the samples by subtherapeutic concentrations of these two drugs. Conclusions: 1) The acid pre-treatment of the samples increases the sensibility of the test of detection of anti-drug antibodies breaking possible drug-antibody complexes. 2)The monitoring of inmunogenicity in patients with subtherapeutic levels of ADL, following a protocol of acid dissociation, has allowed us to detect in a precocious way ADA's presence in these patients contributing to the optimization of the treatment. 3) On the basis of our experience we recommend its application in case of patients with an ADL trough concentration of lower than 2 mg/L following the standard treatment. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3700